Interaction of erythrocytes (RBC's) with nanostructured surfaces - Virk, Harvinder Singh, author; Popat, Ketul C., advisor; Ghosh, Soham, committee member; Li, Vivian, committee member (Colorado State University. Libraries, 2022)
Titanium and its alloys are used to make different blood-contacting medical devices such as stents, artificial heart valves, and catheters for cardiovascular diseases due to their superior biocompatibility. Thrombus formation begins on the surface of these devices as soon as they encounter blood. This leads to the formation of blood clots, which obstructs the flow of blood that leads to severe complications. Recent advancements in nanoscale fabrication and superhydrophobic surface modification techniques have demonstrated that these surfaces have antiadhesive properties and the ability to reduce thrombosis. In this study, the interaction of erythrocytes and whole blood clotting kinetics on superhydrophobic titanium nanostructured surfaces was investigated. These surfaces were characterized for their wettability (contact angle), surface morphology and topography (scanning electron microscopy (SEM)), and crystallinity (glancing angled X-Ray diffraction (GAXRD)). Erythrocyte morphology on different surfaces was characterized using SEM and overall cell viability was demonstrated through fluorescence microscopy. The hemocompatibility of these surfaces was characterized using commercially available assays: thrombin generation assay --> thrombin generation, hemolytic assay --> hemolysis, and complement convertase assay --> complement activity. The results indicate that superhydrophobic titanium nanostructured surfaces had lower erythrocyte adhesion, less morphological changes in adhered cells, lower thrombin generation, lower complement activation, and were less cytotoxic compared to control surfaces. Thus, superhydrophobic titanium nanostructured surfaces may be a promising approach to prevent thrombosis for several blood-contacting medical devices.
Keywords: erythrocytes; hemolysis; thrombin generation; hemocompatibility; complement convertase activity; nanostructured surfaces